Osteogenesis Imperfecta with Celiac Disease and Type II Diabetes Mellitus Associated: Improvement with a Gluten-Free Diet - Luis Rodrigo; Isabel Pérez-Martinez (Case Reports in Medicine)
Osteogenesis imperfecta (OI) is a genetic disease, with a connective tissue alteration, consisting in the presence of multiple spontaneous fractures or after minimal traumatism. Its association with other metabolic processes is rarely described. We present the clinical case of a female adult patient of 43 years. From her infancy, she has had multiple fractures, needing several surgical interventions, and she was diagnosed of OI type 2 at adolescence age. Due mainly to difficulties in walking remaining in wheel-chair in the last three years, she was overweight with morbid obesity (BMI=45.4) and had a type-II DM associated. She suffered from recurrent abdominal pain and chronic diarrhea and was diagnosed of celiac disease (CD) with increased intraepithelial duodenal infiltration, being classified as lymphocytic enteritis, Marsh I type. She was put on a gluten-free diet (GFD), having lost 6 kg of weight after 6 months, with a good control of DM-II and presenting a significant clinical improvement. It is rewarding to search the presence of two coincidental metabolic diseases associated to OI, specially CD, because of the dramatic clinical benefit in the general found after putting on a GFD.